2013
DOI: 10.5733/afin.054.0203
|View full text |Cite
|
Sign up to set email alerts
|

Is Millipede Taxonomy Based on Gonopod Morphology Too Inclusive? Observations on Genetic Variation and Cryptic Speciation inBicoxidens flavicollis(Diplopoda: Spirostreptida: Spirostreptidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
3
5
0
1
Order By: Relevance
“…Although our relatively small taxon sampling, the phylogenetic analysis strongly recovers Sechelleptus as monophyletic and discriminates at least two or three different groups. Furthermore, the mean inter-specific distance values (14.9% for COI and 5.1% for 16S) were remarkably similar to previous studies that reported the presence of high genetic divergence among population of different spirostreptid species (Mwabvu et al 2013(Mwabvu et al , 2015, suggesting the existence of more than one species in those taxa. It is argued that high level of divergence between identified spirostreptid species may indicate that changes in genital morphology occur rather slowly relative to the high rate of substitution in mitochondrial sequences (especially for COI), and may underestimate species diversity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although our relatively small taxon sampling, the phylogenetic analysis strongly recovers Sechelleptus as monophyletic and discriminates at least two or three different groups. Furthermore, the mean inter-specific distance values (14.9% for COI and 5.1% for 16S) were remarkably similar to previous studies that reported the presence of high genetic divergence among population of different spirostreptid species (Mwabvu et al 2013(Mwabvu et al , 2015, suggesting the existence of more than one species in those taxa. It is argued that high level of divergence between identified spirostreptid species may indicate that changes in genital morphology occur rather slowly relative to the high rate of substitution in mitochondrial sequences (especially for COI), and may underestimate species diversity.…”
Section: Discussionsupporting
confidence: 88%
“…The relationships among the outgroups were not the primary focus of the present study, but are consistent with previous studies (Mwabvu et al 2013(Mwabvu et al , 2015Tinago et al 2017) that showed paraphyletic groups suggesting the presence of cryptic species (i.e., Bicoxidens spp.) and possible identification errors in the GenBank database.…”
Section: Phylogenysupporting
confidence: 92%
See 1 more Smart Citation
“…The intra-specific genetic divergences in S. teres reach up to 20.81%, a value above that of Carchesium but distinctly below the 26% threshold in some arthropods 59 . Interestingly, about 19% sequence divergences were observed between two morphologically indistinguishable populations of the millipede Bicoxidens flavicollis 60 . Nonetheless, the present statistical tree topology tests (Supplementary Table S21) and delimitation analyses (Table 1) suggest that at least the population Mdg3 of the S. teres morphospecies might represent a distinct taxon.…”
Section: Discussionmentioning
confidence: 99%
“…Machos possuem o primeiro par de pernas modificado, pênis na coxa do segundo par de pernas e gonópodos (oitavo ou nono par de pernas modificados) para função sexual (Silvestri 1903;Blower 1985;Koch 2015). A identificação de espécies é feita através da morfologia do gonópodo (Hoffman 1980;Jeekel 1985;Mwabvu et al 2013;Enghoff et al 2015). A partir de diferenças relacionadas ao gnatoquilário (originado a partir da primeira maxila) e do gonópodo a ordem é dividida entre as subordens Spirostreptidea e Cambalidea.…”
Section: Sobre a Ordem Spirostreptida Brandt 1833 E Suas Relações Evunclassified